All-dielectric resonant cavity-enabled metals with broadband optical transparency. (18th May 2017) - Liu, Zhengqi; Zhang, Houjiao; Liu, Xiaoshan; Pan, Pingping; Liu, Yi; Tang, Li; Liu, Guiqiang
Abstract: Metal films with broadband optical transparency are desirable in many optoelectronic devices, such as displays, smart windows, light-emitting diodes and infrared detectors. As bare metal is opaque to light, this issue of transparency attracts great scientific interest. In this work, we proposed and demonstrated a feasible and universal approach for achieving broadband optical transparent (BOT) metals by utilizing all-dielectric resonant cavities. Resonant dielectrics provide optical cavity modes and couple strongly with the surface plasmons of the metal film, and therefore produce a broadband near-unity optical transparent window. The relative enhancement factor (EF) of light transmission exceeds 3400% in comparison with that of pure metal film. Moreover, the transparent metal motif can be realized by other common metals including gold (Au), silver (Ag) and copper (Cu). These optical features together with the fully retained electric and mechanical properties of a natural metal suggest that it will have wide applications in optoelectronic devices.